CRITICAL SUCCESS FACTORS AND MODERATING EFFECT OF INNOVATIVE CHARACTERISTICS OF SMES IN EMERGING ECONOMIES: THE CASE OF EGYPT - Wan Rohaida Wan Husain; Haitham Eldalil; Rafikul Islam; Murni Mahmud, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The present study explores the challenges encountered by small and medium enterprises (SMEs) in Egypt, which serves as a model for developing economies. It examines the key factors that substantially impact SME business performance. Additionally, it evaluates the potential moderating role of SME innovative characteristics. The study distributed 400 survey questionnaires to Egyptian SME owners, managers, and executive committee members. The Non-probability Quota Sampling method was applied. Of 400 questionnaires, 360 were returned, giving a 90% response rate. Research variables were tested for reliability and validity using internal consistency, construct validity, and discriminant validity. IBM SPSS AMOS was used for Structure Equation Modelling (SEM) to analyze data and test hypotheses. The study confirmed a strong and positive relationship between government support, financial resources, entrepreneurial skills, and competitiveness with SME business performance. Moreover, it showed how the innovative characteristics significantly strengthen the impact of marketing capabilities on business success. The study illuminates the performance of SMEs in emerging markets. It introduces a new conceptual framework that integrates internal and external critical success factors and examines the potential moderating effect of organizations' innovative characteristics. The study outcomes urge policymakers and stakeholders in developing markets to strengthen and expand their support for SMEs. It emphasizes the crucial role of promoting entrepreneurship and points out the importance of financial institutions in facilitating the provision of grants to SMEs. Similarly, it motivates SME owners to make a concerted effort to improve their skills, foster an innovative culture, and improve eligibility for securing external funding.